2019
DOI: 10.1002/glia.23705
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 synthase modulates macrophage activity and accumulation in injured peripheral nerves

Abstract: We have previously reported that prostaglandin D2 Synthase (L‐PGDS) participates in peripheral nervous system (PNS) myelination during development. We now describe the role of L‐PGDS in the resolution of PNS injury, similarly to other members of the prostaglandin synthase family, which are important for Wallerian degeneration (WD) and axonal regeneration. Our analyses show that L‐PGDS expression is modulated after injury in both sciatic nerves and dorsal root ganglia neurons, indicating that it might play a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 68 publications
(103 reference statements)
1
20
0
Order By: Relevance
“…Sox-2 is also required for proliferation and differentiation of oligodendrocytes during postnatal brain myelination and CNS remyelination [71]. In addition, Sox-2 is a negative regulator of myelination by Schwann cells [20], and its levels are controlled by L-PGDS in PNS injured nerves [22]. We found that Sox-2 expression levels in the hippocampal tissue were quite high (79.4 RPM, Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Sox-2 is also required for proliferation and differentiation of oligodendrocytes during postnatal brain myelination and CNS remyelination [71]. In addition, Sox-2 is a negative regulator of myelination by Schwann cells [20], and its levels are controlled by L-PGDS in PNS injured nerves [22]. We found that Sox-2 expression levels in the hippocampal tissue were quite high (79.4 RPM, Fig.…”
Section: Resultsmentioning
confidence: 93%
“…In vitro studies also demonstrated that L-PGDS acts as a disaggregase by disassembling Aβ fibrils [30]. In the PNS, L-PGDS contributes to myelination during development [63], and potentially acts as an antiinflammatory agent under conditions of peripheral nerve injury [22]. In the latter studies, L-PGDS modulated the expression of the transcription factor Sox-2, which in the CNS regulates oligodendrocyte proliferation and differentiation [71], and in the PNS is a negative regulator of myelination [20, 22].…”
Section: Discussionmentioning
confidence: 99%
“…L-PGDS is necessary for macrophage activity and myelin debris clearance in a non-cell autonomous way during the resolution of PNS injury. In late phases of Wallerian degeneration, L-PGDS regulates the bloodnerve barrier permeability and SOX2 expression in Schwann cells, prevents macrophage accumulation, and exerts an antiinflammatory role (Forese et al, 2020). Thus, L-PGDS has a different role during development and after injury in the PNS.…”
Section: Lipocalin-type Prostaglandin D 2 Synthase In Peripheral Nervous Systemmentioning
confidence: 99%
“…Macrophages can also be recruited to sensory and sympathetic ganglia after injury in response to increased expression of CCL2 by axotomized neurons, where they participate in the activation of a transcriptional program in the neurons that promotes neurite outgrowth (Cattin & Lloyd, 2016;Kwon et al, 2013Kwon et al, , 2015Niemi, DeFrancesco-Lisowitz, Cregg, Howarth, & Zigmond, 2016;Niemi et al, 2013;Zigmond & Echevarria, 2019). In addition, prostaglandin D2 synthase, potentially via its expression in neurons, has recently been shown to modulate macrophage activity and accumulation after nerve injury (Forese et al, 2020).…”
Section: Axonal Breakdown and Schwann Cell Transdifferentiationmentioning
confidence: 99%